2016
DOI: 10.1080/13685538.2016.1220519
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between: occupational status, biological condition and androgen hormone level among Polish adult men: the Wroclaw Male Study

Abstract: Population health and its determinants are one of the major challenges to social and economic policy. The aim of this study was to investigate the relationship between occupational activity and biological condition in adult working Polish men. The participants of the study were 300 men (30-65 years), healthy inhabitants of the city of Wroclaw, Poland. Seventeen measures of biological condition were examined. The subjects were divided into three different occupational groups: professionals, soldiers and skilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
(49 reference statements)
1
9
0
1
Order By: Relevance
“…A comparison of biological age and biological parameters showed that professionals and soldiers had a lower biological age than skilled workers. In all groups, chronological age correlated negatively and significantly with IGF-1, FT, E2, and DHEAS [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison of biological age and biological parameters showed that professionals and soldiers had a lower biological age than skilled workers. In all groups, chronological age correlated negatively and significantly with IGF-1, FT, E2, and DHEAS [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies involving men measured T or TT levels in relation to age, whereas some also analyzed DHEAS [ 11 , 15 ], IGF-1 [ 13 , 15 ], BMI [ 10 ], type of work [ 12 , 14 , 15 , 16 , 17 , 18 ], andropause symptoms (with the AMS scale [ 12 , 14 ]), job content (with the JCQ questionnaire [ 12 , 14 ]), lifetime SEP [ 13 ], and sleep disorders [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The material for the study consisted of sociological and biomedical data of 355 men aged 32-87 years, randomly invited to the study as part of the Wroclaw Male Study research project (WMS) [20,[31][32][33][34][35]. The men were active, healthy inhabitants of the city of Wroclaw (Poland, Lower Silesia, population in 2010: 632,996, including men: 294,960), and they were medically examined in 2000 and in 2010/11 under the WMS research project in the Lower Silesian Medical Centre DOLMED S.A. in Wroclaw (Poland).…”
Section: Samplementioning
confidence: 99%